The study of Postmodern Language Components in the Story "Passing again through the Same Streets" by Bijan Najdi - Abdollah Hasanzadeh mirali; Ghazaleh Heidari Abkenar (مطالعات زبانی و بلاغی)
One of the main characteristics of story writing in sixth and seventh decades in Iran is, trying to open new doors to the story world and increase the level of story writing. Among the efforts made between storywriters in these two decades, a few works of Bijan Najdi have a special position, since his works are pose as the important background of presentation and genesis of postmodernism approach in the Iranian contemporary story writing. In the present study, we try to present both the postmodernism analysis on the short story "Passing again through the same streets" by Bijan Najdi, and also determine the rhetorical elements related to postmodernism and their relationship with Najdi's poetry. For this purpose, first; postmodernism and the main components of its fiction such as short circuit, metanarrative, ontological content, grand narrative collapse, and … are represented, replying on critical criticism theory in this field such as, David Lodge, Peter Shia, and Barry Louis, and then the existence of each components is proved with samples from stories. It can be argued that, in addition to the fact that the presence of these components together, suggests the postmodernism of this work, the rhetorical elements have also added to the poeticism in the form of exaggeration and irony indices.